FACTORS AFFECTING TRANSFER PRICING AGGRESSIVENESS IN INDONESIAN MULTINATIONAL COMPANY - Setyarini Santosa; Fabiola Hagai Karina (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2022)
Transfer pricing has been cited as the most crucial tax avoidance issue in multinational company. Transfer pricing is defined as the price to buy or sell goods and services between related parties. This kind of transaction may be conducted by a person or an entity that has special relationship with the company which might against the arm’s length principle. As many issues have been arisen regarding tax avoidance through transfer pricing practices, this study wants to examine the major determinants of transfer pricing aggressiveness in multinational company listed on Indonesia Stock Exchange for year 2013-2017. Sampling method used in this study is purposive sampling. Based on hand-collected sample of 120 publicly-listed Indonesian multinational company, through multiple regression analysis, the result shows that tax expense does not affect multinational company’s aggressiveness to do transfer pricing, while exchange rate, share ownership, leverage and firm size affect multinational company’s aggressiveness to do transfer pricing.